2014
DOI: 10.1074/jbc.m114.601310
|View full text |Cite
|
Sign up to set email alerts
|

AMPylation of Rho GTPases Subverts Multiple Host Signaling Processes

Abstract: Background: VopS is a bacterial effector that AMPylates Rho GTPases. Results: AMPylation of Rho GTPases inhibits their interaction with multiple downstream effectors. Conclusion: VopS conducts a multifaceted host signaling inhibition program by targeting the critical Rho GTPases. Significance: Broadens the understanding of how switch-1 modification of Rho GTPases affects host responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 40 publications
2
51
0
Order By: Relevance
“…However, the switch I loop mediates the interaction of small GTPases with several downstream signaling partners, and therefore, AMPylation of this region is expected to alter a variety of cellular processes. Woolery and others [96] showed that VopS also inhibits the activation of pro-inflammatory and cell survival signaling pathways, such as NFkB and the mitogen-activated protein kinases JNK and Erk. In corroboration with these findings supporting a role for VopS in subversion of pro-inflammatory immune responses, VopS (and also VopQ) was shown to suppress inflammasome assembly as a result of bacterial activation of the nucleotide-binding oligomerization domain receptors (NOD-like receptors or NLRs) [97].…”
Section: Vopsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the switch I loop mediates the interaction of small GTPases with several downstream signaling partners, and therefore, AMPylation of this region is expected to alter a variety of cellular processes. Woolery and others [96] showed that VopS also inhibits the activation of pro-inflammatory and cell survival signaling pathways, such as NFkB and the mitogen-activated protein kinases JNK and Erk. In corroboration with these findings supporting a role for VopS in subversion of pro-inflammatory immune responses, VopS (and also VopQ) was shown to suppress inflammasome assembly as a result of bacterial activation of the nucleotide-binding oligomerization domain receptors (NOD-like receptors or NLRs) [97].…”
Section: Vopsmentioning
confidence: 98%
“…Rac also composes the NADPH oxidase complex, which generates reactive oxygen species at the site of bacterial engulfment by phagocytes. VopS-mediated AMPylation of Rac blocks the association of the GTPase with the complex and therefore allows bacterial escape from killing by phagocytes [96].…”
Section: Vopsmentioning
confidence: 99%
“…Identification of HYPE substrates with roles in UPR, ATP biosynthesis/transport, and gene expression as well as several members of the tubulin family (TUBB, TUBB4B) that are major constituents of microtubules provides interesting hypothesis that AMPylation by HYPE could be an important regulator of ER stress in eukaryotic cells. In addition, AMPylation of tubulins and potential involvement in microtubule biology could point to further implication of AMPylation in the maintenance of the cytoskeleton-an interesting perspective taking into account the fact that bacterial AMPylation of Rho GTPases also targets the cytoskeleton, with detrimental consequences for the infected cell (44). Our experimental evidence clearly excludes small GTPases as substrates of eukaryotic AMPylation in vitro, as supported by recent reports under physiological conditions (15) pointing to the conclusion that AMPylation is under stringent control within the eukaryotic cell.…”
Section: Discussionmentioning
confidence: 99%
“…1) 8,9 , AMPylation could regulate many potential functions in a variety of cellular processes 3,4,1012 . For example, Yarbrough and Woolery found that a bacterial Fic AMPylator, VopS, modifies host Rho GTPases, blocks their interaction to downstream targets and alters NFκB, Erk and JNK signaling 3,11,13 . Using the fly as a genetic model, Rahman revealed that Drosophia Fic (dFic) controlled visual neurotransmission and the flies became blind with the ablation of dFic by mutations 12 .…”
Section: Introductionmentioning
confidence: 99%